Fabricating controllable hierarchical pores on smooth carbon sheet for synthesis of supercapacitor materials. (October 2019) - Liu, Man; Qin, Zhihong; Yang, Xiaoqin; Lin, Zhe; Guo, Tong
Abstract: A smooth and defectless carbon sheet with thickness of 1–2 μm was prepared by loose medium component from coal. Then, porous carbon sheet materials were prepared by activation of the carbon sheet using KCl and KOH under 750 °C and N2 atmosphere. Such materials have lattice defect and porous structure which were verified by emission scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman and N2 adsorption-desorption. Their electrochemical performances were studied by cyclic voltammetry curves and constant current charge-discharge curves. The results showed that varing the content of KCl could control the distribution of the mesopore so as to change the specific capacitance. When carbon/KCl/KOH was at a mass ratio of 1:3:4, the specific capacitance reached up to 346 F g −1 at the current density of 0.1 A g −1 with high energy density and power density of 12 Wh kg −1 and 25 W kg −1, respectively. The high specific capacitance of this material was corresponded to its porous structure with high specific surface area of 3627 m 2 g −1 . Based on the above structure features and performance results, this paper supplies a brand new and promising way for synthesis of supercapacitor materials. Highlights: Coal was used to form smooth carbon sheets that are etched into pores. KCl did not act as a pore-creating agent on the carbon sheets, but act as an adjuvant when added with KOH. The specific surface area of the porous activated carbon sheet was up to 3627 m 2 g −1 . The electrochemical properties were up to 346 F g −1 at 0.1 A g −1 .